2013
DOI: 10.1597/11-127
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Social Factors in Undergoing Reconstructive Surgery among Individuals with Craniofacial Conditions: An Exploratory Study

Abstract: Objective Reconstructive surgery to improve psychological well-being is commonly offered to children with craniofacial conditions. Few studies have explored the challenges of reconstructive surgery beyond the physical risks: poor treatment outcomes, infection, brain damage, and death. This qualitative study aims to understand the psychological and social implications such interventions can have for individuals with craniofacial conditions. Design A total of 38 individuals between the ages of 12 and 61 with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Many individuals with those deformities face problems with self‐esteem and difficulties forming relationships with others (Sousa, Devare, & Ghanshani, ). Qualitative studies on individuals with cleft lip/palate have reported higher incidences of being subjected to teasing and social isolation, which have led to a decline in social behaviour and, overall, a reduced quality of life (Bemmels et al, ; Chetpakdeechit, Hallberg, Hagberg, & Mohlin, ). A study that investigated Norwegian adults showed that individuals with complete cleft lip and palate (CLP) experienced twice as much anxiety, depression and palpitations, as those without CLP (Ramstad, Ottem, & Shaw, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many individuals with those deformities face problems with self‐esteem and difficulties forming relationships with others (Sousa, Devare, & Ghanshani, ). Qualitative studies on individuals with cleft lip/palate have reported higher incidences of being subjected to teasing and social isolation, which have led to a decline in social behaviour and, overall, a reduced quality of life (Bemmels et al, ; Chetpakdeechit, Hallberg, Hagberg, & Mohlin, ). A study that investigated Norwegian adults showed that individuals with complete cleft lip and palate (CLP) experienced twice as much anxiety, depression and palpitations, as those without CLP (Ramstad, Ottem, & Shaw, ).…”
Section: Introductionmentioning
confidence: 99%
“…1 When facial reconstructive surgery is the treatment of choice for patients with craniofacial conditions, improved physical appearance is the goal with the spoken or unspoken hope that this change in appearance will result in an improved quality of life. 2–4 Research has demonstrated that a technically well-performed surgery does not necessarily result in a satisfied patient. 4,5 However we do not really understand how a patient develops their sense of satisfaction or disappointment.…”
mentioning
confidence: 99%
“…2–4 Research has demonstrated that a technically well-performed surgery does not necessarily result in a satisfied patient. 4,5 However we do not really understand how a patient develops their sense of satisfaction or disappointment. The disconnect between the assumed benefit of improved appearance on quality of life with evidence that a successful surgical experience does not necessarily lead to a satisfied patient points to the need for a closer look at these issues.…”
mentioning
confidence: 99%
See 2 more Smart Citations